Disaster Health After The 2011 Great East Japan Earthquake. Issue 1 (22nd January 2014) - Kako, Mayumi; Arbon, Paul; Mitani, Satoko
Abstract Introduction The March 11, 2011 disaster was unparalleled in the disaster history of Japan. There is still enormous effort required in order for Japan to recover from the damage, not only financially, but psychosocially. This paper is a review of the studies that have been undertaken since this disaster, from after the March 11th disaster in 2011 to the end of 2012, and will provide an overview of the disaster-health research literature published during this period. Methods The Japanese database Ichushi Ver. 5 was used to review the literature. This database is the most frequently used database in Japanese health-sciences research. The keywords used in the search were "Higashi Nihon Dai-shinsai" (The Great East Japan Earthquake). Results A total of 5, 889 articles were found. Within this selection, 163 articles were categorized as original research (gencho ronbun). The articles were then sorted and the top four key categories were as follows: medicine (n = 98), mental health (n = 18), nursing (n = 13), and disaster management (n = 10). Additional categories were: nutrition (n = 4), public health (n = 3), radiology, preparedness, and pharmacology (n = 2 for each category). Nine articles appeared with only one category label and were grouped as "others." Conclusion This review provides the current status of disaster-health research following the Great East Japan Earthquake. The research focus over the selected period was greatly directed towards medical considerations, especially vascular conditions and renal dialysis. Considering the compounding factors of the cold temperatures at the time of the disaster, the geography, the extensive dislocation of the population, and the demographics of an aging community, it is noteworthy that the immediate and acute impact of the March 11th disaster was substantial compared with other events and their studies on the impact of disaster on chronic and long-term illness. The complexity of damage caused by the earthquake event and the associated nuclear power plant event, which possibly affected people more psychologically than physically, might also need to be investigated with respect to long term objectives for improving disaster preparedness and management. <mixed-citation id="ref" publication-type="journal"> <string-name> <given-names>M</given-names> <x content-type="archive" xml:space="preserve"> </x> <surname>Kako</surname> </string-name>, <string-name><given-names>P</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Arbon</surname></string-name>, <string-name><given-names>S</given-names><x content-type="archive" xml:space="preserve"> </x><surname>Mitani</surname></string-name>. Literature review on disaster health after the 2011 Great East Japan Earthquake . <source>Prehosp Disaster Med</source>. <year>2014</year>;<volume>29</volume>(<issue>1</issue>):<fpage>1</fpage>-<lpage>6</lpage></mixed-citation>.